Isolation and characterization of a monoclonal antibody containing an extra heavy-light chain Fab arm. Issue 3 (3rd April 2018) - Boyd, Dan; Ebrahimi, Arpa; Ronan, Sarah; Mickus, Brian; Schenauer, Matthew; Wang, Jenny; Brown, Darren; Ambrogelly, Alexandre
ABSTRACT: Isolation and characterization of monoclonal antibody (mAb) variants to understand the impact of their structure on function is a typical activity during early-stage candidate selection that contributes to derisking clinical development. In particular, efforts are devoted to characterizing oligomeric variants, owing to their potential immunogenic nature. We report here a mAb variant consisting of a canonical mAb monomer associated in a non-covalent fashion with an antigen-binding fragment (Fab) arm amputated from its Fc domain. The truncated heavy chain is encoded in the cell line genome and is the likely product of a genomic recombination during cell line generation. The addition of the Fab arm results in severe loss of potency, indicating its interaction with the Fab domain of the monomer. The presence of such a variant can easily be mitigated by an adequate purification step.